Household Appliances Dropship Business (Me Home) - Sani Kurnia; Dessy Aliandrina (ConCEPt - Conference on Community Engagement Project, 2023)
This study focuses on the dropship business that sells household appliances online on the Tokopedia marketplace. The business name is Me Home. The problems in the dropship business include the small number of suppliers, less varied products, and product promotion on social media. The scope of this study is the addition of provider partners and product catalog creation. The purpose of this activity is to find suitable supply partners, create catalogs, and increase product sales in the Me Home dropshipping business. The target of this dropship business activity is to increase the number of supply partners, design product catalogs, and add business promotional media. The research methodology used is a qualitative research methodology. Data collection techniques using semi-structured interviews. The selected informants were sellers of household appliances and buyers of household appliances. The results obtained after carrying out this activity are increasing the number of suppliers in the dropship Me Home business, having a catalog, and using social media as a marketing tool.